Luminescence of Eu3+ in GaN(Mg, Eu): Transitions from the 5D1 level - Singh A.K.; O'Donnell K.P.; Edwards P.R.; Cameron D.; Lorenz K.; Kappers M.J.; Boćkowski M.; Yamaga M.; Prakash R. (My University, 2025)
Eu-doped GaN(Mg) exemplifies hysteretic photochromic switching between two configurations, Eu0 and Eu1(Mg), of the same photoluminescent defect. Using the above-bandgap excitation, we studied the temperature dependence of photoluminescence (TDPL) of transitions from the excited 5D1 level of Eu3+ for both configurations of this defect. During sample cooling, 5D1→7F0,1,2 transitions of Eu0 manifest themselves at temperatures below ∼200 K, while those of Eu1(Mg) appear only during switching. The observed line positions verify crystal field energies of the 7F0,1,2 levels. TDPL profiles of 5D1→7F1 and 5D0→7FJ transitions of Eu0 show an onset of observable emission from the 5D1 level coincident with the previously observed, but hitherto unexplained, decrease in the intensity of its 5D0→7FJ emission on cooling below 200 K. Hence, the 5D0→7FJ TDPL anomaly signals a back-up of 5D1 population due to a reduction in phonon-assisted relaxation between 5D1 and 5D0 levels at lower temperatures. We discuss this surprising result in the light of temperature-dependent transient luminescence measurements of Eu0. © 2017 Author(s).